RESPON PERTUMBUHAN DAN HASIL BAWANG MERAH (Allium ascalonicum L.) TERHADAP PEMBERIAN MULSA ORGANIK DAN PUPUK NPK PADA TANAH ULTISOL - Pandedi, Pandedi; S, Zubaidah; P, Surawijaya (Fakultas Pertanian Universitas Palangka Raya, 2020)
This study aims to determine the effect of organic mulch treatment and NPK fertilizer application in increasing the growth and yield of onions on ultisol soils. The study used a factorial randomized complete block design consisting of two factors. The first factor was the treatment of organic mulch consisting of 4 levels of treatment M0 = control, M1 = grass mulch, M2 = sawdust mulch, M3 = mulch fern. The second factor is NPK fertilizer consisting of 5 treatment levels N0 = Control, N1 = NPK (200 kg ha-1) or 15.0 g plot-1, N2 = NPK (300 kg ha-1) or 22.5 g plot-1 , N3 = NPK (400 kg ha-1) or 30.0 g plot-1, N4 = NPK (500 kg ha-1) or 37.5 g plot-1, repeated 3 times, so that obtained 60 trial plots. The study was conducted in March to June 2017, located at the Agricultural Counseling Center, Kuala Kurun Gunung Mas Regency. The results of the study showed that the interaction of organic mulch and NPK compound fertilizer did not significantly affect all observational parameters. The provision of organic mulch had a significant effect on plant height, weight tubers per clump and tuber weights per plot. The M1 (grass) treatment gave the highest plant height of 26.7 cm (5 MST) and tuber weights 229.7 g plot-1. The highest yield per tuber cluster in M2 (sawdust) is 24.7 g. NPK fertilizer application has a significant effect on plant height and tuber weight per clump. The N2 treatment (300 kg ha-1) gave the highest plant height of 25.3 cm, while the N3 treatment (400 kg ha-1) gave the highest yield on tuber weight per cluster of 24.5 g